Fibromatosis of the accessory breast mimicking a malignant tumor: a rare case report and literature review - Li, Jing; Qi, Chaoyi; Liu, Yixiao; Xu, Jiahuan; Cao, Lei; Hu, Yanyan; Wang, Jian (Frontiers in Oncology, 2025)
Fibromatosis is a rare neoplasm characterized by fibroblastic and myofibroblastic proliferation. Fibromatosis that occurred in the accessory breast has never been reported in the literature worldwide. We present a case of extra-abdominal fibromatosis of the accessory breast occurring in a 36-year-old Chinese female patient. The tumor was hard with unclear boundaries and adhered to surrounding tissues (6 × 4 × 3 cm). Despite that malignancy was initially suspected based on clinical, ultrasound, and magnetic resonance imaging (MRI) results, histopathology and immunohistochemistry showed an unexpected outcome. At the 2-year postoperative follow-up, there was no recurrence; the prognosis was explained to the patient. This case emphasizes the importance of clinical suspicion and histopathological evaluation and the need to raise awareness to promote early diagnosis and appropriate management of fibromatosis. We also present a literature review of varied presentations and treatment options for extra-abdominal fibromatosis.